Fluence perturbation from fiducial markers due to edge-scattering measured with pixel sensors for 12C ion beams. (17th April 2020) - Reidel, Claire-Anne; Schuy, Christoph; Horst, Felix; Ecker, Swantje; Finck, Christian; Durante, Marco; Weber, Uli
Abstract: Fiducial markers are nowadays a common tool for patient positioning verification before radiotherapy treatment. These markers should be visible on x-ray projection imaging, produce low streak artifacts on CTs and induce small dose perturbations due to edge-scattering effects during the ion-beam therapy treatment. In this study, the latter effect was investigated and the perturbations created by the markers were evaluated with a new measurement method using a tracker system composed of six CMOS pixel sensors. The present method enables the determination of the particle trajectory before and after the target. The experiments have been conducted at the Marburg Ion Beam Therapy Center with carbon ion beams and the measurement concept was validated by comparison with radiochromic films. This work shows that the new method is very efficient and precise to measure the perturbations due to fiducial markers with a tracker system. Three dimensional fluence distributions of all particle trajectories were reconstructed and the maximum cold spots due to the markers and their position along the beam axis were quantified. In this study, four small commercial markers with different geometries and materials (gold and carbon-coated ZrO2 ) were evaluated. The gold markers showed stronger perturbations than the lower density ones. However, it is important to consider that low density and low atomic number fiducial markers are not always visible on x-ray projections.